STUDY OF THE ELEMENTARY BASE OF THE SETTLEMENT SYSTEMS - Zastavetska, Lesia (Human Geography Journal, 2016)
The article analyzes current changes that occur in the elementary structure of the settlement systems and also reflects the methodology of their study. Special attention is paid to the methodology of studying the directionality and intensity of relations between the settlements, dynamics of reciprocal development of the settlements in the system, homogeneity degree of the network of populated areas.  All of the abovementioned provides an opportunity to establish the boundaries of the settlement system and allocate the nucleus of the system in the future. Investigation of the development level of the settlements’ functions is the foundation for the establishment of their role in the settlement system, particularly the centrality or peripherality of the settlement.